Prime Time Light Exposures Do Not Seem to Improve Maximal Physical Performance in Male Elite Athletes, but Enhance End-Spurt Performance - Knaier, Raphael; Schäfer, Juliane; Rossmeissl, Anja; Klenk, Christopher; Hanssen, Henner; Höchsmann, Christoph; Cajochen, Christian; Schmidt-Trucksäss, Arno (Frontiers in Physiology, 2017)
Many sports competitions take place during television prime time, a time of the day when many athletes have already exceeded their time of peak performance. We assessed the effect of different light exposure modalities on physical performance and melatonin levels in athletes during prime time. Seventy-two young, male elite athletes with a median (interquartile range) age of 23 (21; 29) years and maximum oxygen uptake (VO2max) of 63 (58; 66) ml/kg/min were randomly assigned to three different light exposure groups: bright light (BRIGHT), blue monochromatic light (BLUE), and control light (CONTROL). Each light exposure lasted 60 minutes and was scheduled to start 17 hours after each individual’s midpoint of sleep (median time: 9:17 pm). Immediately after light exposure, a 12-minute time trial was performed on a bicycle ergometer. The test supervisor and participants were blinded to the light condition each participant was exposed to. The median received light intensities and peak wavelengths (photopic lx/nm) measured at eye level were 1319/545 in BRIGHT, 203/469 in BLUE, and 115/545 in CONTROL. In a multivariate analysis adjusted for individual VO2max, total work performed in 12 minutes did not significantly differ between the three groups. The amount of exposure to non-image forming light was positively associated with the performance gain during the time trial, defined as the ratio of the work performed in the first and last minute of the time trial, and with stronger melatonin suppression. Specifically, a tenfold increase in the exposure to melanopic light was associated with a performance gain of 6.2% (95% confidence interval: 1.3, 11.1; P=0.013) and a melatonin decrease of -0.9 pg/ml (95% confidence interval: -1.5, -0.3; P=0.006). Exposure to bright or blue light did not significantly improve maximum cycling performance in a 12-minute all-out time trial. However, it is noteworthy that the estimated difference of 4.1 kJ between BRIGHT and CONTROL might represent an important performance advantage justifying further studies. In conclusion, we report novel evidence that evening light exposure, which strongly impacts the human circadian timing system, enables elite athletes to better maintain performance across a 12-minute cycling time trial.